APLIKASI SISTEM REGISTRASI AKUN OFFICE 365 ONLINE UPT. ICT CENTER UNM - Muhammad Agung; Muhammad Mahdinul Bahar; Rusli Ismail; Baso Riadi Husda (AGENTS: Journal of Artificial Intelligence and Data Science, 2022)
The account registration system of Office 365 UNM. is a support system for the distribution of Office 365 accounts for students, lecturers, and UNM employees within the Makassar State University. This system is expected to make it easier for admins to validate the data of students, lecturers, and UNM employees who register for an Office 365 account. Microsoft Office 365 includes Office Online (Word, PowerPoint, Excel, and OneNote), unlimited OneDrive storage, SharePoint sites, and Yammer. This study aims to build a registration and administration system to get an Office 365 account. In addition, to see the efficiency and effectiveness of service management work provided by the university and the process of developing this information system using the waterfall development method, using DFD to document, specify and model system. Implemented using the PHP programming language with support for Jquery, Javascript and MYSQL on Codeigneter Freamwork and other supporting software. The results of this research are expected to produce an Office 365 account registration system. The implementation of this registration system, the distribution and validation process for Office 365 accounts will be right on target, effective and efficient. This application has very good quality with 86.51% to highest ideal score.